Observation of effect of hemodiafiltration on sleep and quality of life score and sleep quality in maintenance hemodialysis patients - WANG Dong; LIU Lei; WEI Ming-ming; LI Xin-jian; LIU Jia-hui (Linchuang shenzangbing zazhi)
Objective To observe effect of hemodiafiltration(HDF) on sleep and life quality in those patients with maintenance hemodialysis(HD). Methods Seventy maintenance hemodialysis(MHD) patients were selected and randomly divided into conventional HD group(HD group)and On-line HDF group(HDF group), with 35 cases in each group. In the HD group all the patients were adjusted to receivehemodialysis three times every week; and in the HDF group, all the patients received conventional hemodialysis twice and HDF once every week,with duration of 4 hours. Pittsburgh sleep quality index(PSQI) and health status questionnaire(SF-36) score improvement were compared between the two groups. Results After treatment, total PSQI scores(including sleep latency, sleep duration, sleep efficiency) and the SF-36 scores(including bodily pain, general health, vitality, role-emotional, mental health) showed significant improvement compared to those before treatment. Sleep latency, sleep duration and sleep efficiency and total PSQI scores after treatment in the HDF group had greater improvement than those in the HD group(P<0.05); bodily pain(BP), general health(GH), vitality(VT),role-emotional(RE)and mental health(MH) scores in the HDF group were significantly lower than those in the HD group after treatment(P<0.05). Conclusions HDF may improve sleep and life quality better in patients with maintenance hemodialysis.